Propuesta de implementación de una oficina de proyectos (PMO) de control en la empresa Inframetel en la ciudad de Quito, midiendo su resultado a través de una prueba piloto en un proyecto - Velasco Alarcón, Luis Alberto (2018)
This research has the purpose of implementing an Office of Project Management of Control (PMO) in the company IMFRAMETEL, in order to improve the performance and results, as well as the culture of project management, and the development of the management from the Project Management Office (PMO). Among the specific objectives that serve as a guide for the development of the proposal are: Identify the different aspects of the management philosophy of the Imframetel company; Diagnosis of the current situation in the management of projects in the organization; Carry out an analysis of the cause and effect of the different situations in which the project management of the company can be carried out. Imframetel: Design the management model of the Project Management Office (PMO); Validate the PMO model by accompanying the management of a pilot project; and Measurement of the results of the management model of the PMO. These objectives will be reflected in the management of the installation of the PMO control office in the company INFRAMETEL in the city of Quito.